1989
DOI: 10.1083/jcb.108.4.1557
|View full text |Cite
|
Sign up to set email alerts
|

The hyaluronate receptor is preferentially expressed on proliferating epithelial cells.

Abstract: Abstract. In the present study, we have examined the distribution of the hyaluronate receptor as well as hyaluronate itself in a variety of adult tissues. The hyaluronate receptor was localized with a monoclonal antibody, termed K-3, while hyaluronate was localized using proteolytic fragments of cartilage proteoglycan. Staining with the K-3 monoclonal antibody revealed that the hyaluronate receptor was present in a variety of epithelia including the skin, cheek, tongue, esophagus, vagina, intestines, oviduct, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
98
1
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(109 citation statements)
references
References 27 publications
9
98
1
1
Order By: Relevance
“…Association of IpaB with these receptors could therefore explain the polarity of the entry process, which is essentially basolateral . Such interactions could also explain the preferential tropism of Shigella in vivo (Perdomo et al, 1994), as CD44 displays a basolateral distribution, particularly in the immature cells of intestinal crypts (Alho and Underhill, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Association of IpaB with these receptors could therefore explain the polarity of the entry process, which is essentially basolateral . Such interactions could also explain the preferential tropism of Shigella in vivo (Perdomo et al, 1994), as CD44 displays a basolateral distribution, particularly in the immature cells of intestinal crypts (Alho and Underhill, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Alho and Underhill (44) have shown that CD44 is expressed on a variety of different epithelia in vivo but that it is particularly noted in rapidly proliferating cells, which may have a crucial role in epithelial maturation. We have also observed an accentuated staining pattern of CD44 IR observed in reactive (45) and highly proliferative urothelium, associated with previous therapy (45).…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, los niveles de áci-do hialurónico se elevan en forma dramática inmediatamente después de la lesión tisular (10). El ácido hialurónico puede estar unido a receptores que están preferentemente localizados en regiones de crecimiento celular activo (11).…”
Section: áCido Hialurónico Y Lesión Tisularunclassified